Online Festival as Method for A Network for Action and Well-Being for Disability and All based on CRPD and SDG2030 - Nuah Perdamenta Tarigan (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
Being happy is the dream of all humans, not looking at gender, including not looking at whether they are disabled or not. People often look down on people with disabilities including the elderly who are often marginalized in society. They are often considered not citizens who have the same rights and obligations as the general public. CRPD or the Convention on the Rights of Persons with Disabilities regulated in Act Number 8 of 2016 concerning Persons with Disabilities in the territory of the Republic of Indonesia is very different from the disability law approach that was previously based on mercy or charity and SDG 2030. Especially in the context of the current Coronavirus or Covid19 pandemic. Those who are vulnerable in this case, people with disabilities and elderly are very at risk. Especially in the aforementioned laws, the latest paradigm is based more on human rights? The theme of this research paper is related to the view of the fundamental right to get happiness. We will see the happiness of my friends with disabilities in "staying at home" situations. Will they feel part of the community if they are included in an online multicultural cultural festival? Indeed, it is one of the movements that can be built, following the disability movement so far that has used cultural festivals as one of the movements used to advocate for existing disability rights with disabilities, but in reality, they have not been given a proper place to they are, with sincerity. Several obstacles have occurred up to now, both in terms of health, education, social welfare, accessibility, and others. Hopefully, in the future network actions will not only occur between people with disabilities, but also online multicultural campaigns and festivals or not and between people with disabilities and the general public will have a more significant and sustainable future impact.